Physical, intrapersonal and interpersonal benefits of playground interventions in primary education - Méndez-Giménez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The increase in sedentary and child obesity rates worries internationally. Data from Spain reveal an alarming increase in the prevalence of childhood and adolescent obesity, which reaches 15.9% in children aged 6 to 9 years. Compulsory schooling has the potential to alleviate this pandemic and to promote active habits among all schoolchildren, with a relatively low effort and cost. This requires the implementation of intervention programs and effective strategies. This study reviews the research evidence that has analyzed the impact of interventions on recess time applied in primary schools not only at a physical level (physical activity) but also at the intrapersonal (e.g., motivation, behavior, individual attitudes, etc.) and interpersonal level (e.g., social relationship). It is concluded that multi-component programs (several intervention strategies) and those that serve different strata of influencing factors are more effective and complete than uni-component interventions (only one strategy). Finally, practical implications are suggested for principals and teachers.